The effect of Ti on precipitation of fully coherent DO22 superlattice in an Ni-Cr-W-based superalloy. (June 2017) - Gao, Xiangyu; Hu, Rui; Luo, Gongliao
Abstract: The ordering reaction in the newly developed Ni-Cr-W-Ti alloy aged at 700 °C has been investigated using atom probe tomography and transmission electron microscopy. The results reveal that the existence of titanium in the superalloy induces and stabilizes the DO22 superlattices, which cannot precipitate in the ternary Ni-Cr-W superalloy. The stoichiometry of the DO22 phase has been determined to be Ni3 (Cr0.2 W0.4 Ti0.4 ), and the interfaces between DO22 precipitates and matrix have been revealed to be fully coherent at the atomic scale. Graphical abstract: